Reliability and validity analysis of indoor air quality, crew stress level and self efficacy in warship environment: a pilot survey - Abdul Halim, Muhammad Hisham; Ismail, Asmat; Md Sakip, Siti Rasidah (Universiti Teknologi MARA, Perak, 2025)
Warship environments present unique challenges to personnel, including concerns about indoor air quality (IAQ). There are physical symptoms and health effects associated with poor IAQ, which affect crew stress levels. Both variables were proportionately influenced by crew self-efficacy. Previous research demonstrates a lack of holistic studies of the relationship between IAQ, self-efficacy, and crew stress levels on board warships. Hence, further studies regarding the instrument’s effectiveness in measuring all variables would be worthwhile. Thus, this study aims to evaluate the reliability and validity of the instrument to measure IAQ, crew stress level, and self-efficacy amongst warship crew by utilizing data collected from a pilot survey using the Statistical Package for the Social Sciences (SPSS). Reliability and validity of measurement variables using content validity and reliability method. The content validity assessment was carried out by three experts, including the researcher's supervisor and the Director of Malaysia Armed Forces Physiology and Counselling. Consequently, the researcher invited ten personnel with experience serving onboard KD JEBAT to participate in the face validity process. Data were collected from a sample of 52 warship personnel, and reliability analyses were conducted using Cronbach's alpha coefficient to assess the internal consistency of each dimension. Corrected item-total correlations were also examined to evaluate the relationship between individual survey items and their respective constructs. The reliability analysis revealed an internal consistency (acceptable to good levels) within variables which is IAQ, crew stress level, and self-efficacy. However, the stress-triggered dimension exhibited a lower reliability coefficient. Additionally, the corrected item-total correlations provide a significant relationship between items and corresponding constructs in support of the validity of the measurement scales. As a result, all items were accepted and valid to conduct actual survey with the value of Cronbach's alpha for dimension (a) Indoor Air Contaminant Parameter (0.747), (b) Indoor Air Physical Parameter (0.708), (c) Stress Response (0.715), (d) Stress Triggered (0.703), (e) Victorious Experience (0.780), (f) Performance Outcome (0.705). The researcher utilizes the analysis results to design the best questionnaire survey for the actual survey. Future research may enhance the understanding of this domain and contribute to the betterment of warship personnel.